2017
DOI: 10.1080/03630242.2017.1306607
|View full text |Cite
|
Sign up to set email alerts
|

Multiple levels of social influence on adolescent sexual and reproductive health decision-making and behaviors in Ghana

Abstract: Little is known about the multilevel social determinants of adolescent sexual and reproductive health (SRH) that shape the use of family planning (FP) among young women in Africa. We conducted in-depth, semi-structured, qualitative interviews with 63 women aged 15–24 years in Accra and Kumasi, Ghana. We used purposive, stratified sampling to recruit women from community-based sites. Interviews were conducted in English or local languages, recorded, and transcribed verbatim. Grounded theory-guided thematic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 35 publications
(39 reference statements)
5
74
0
2
Order By: Relevance
“…However, for mothers who experienced challenges and side effects discouraged other mothers from using IUD. This is in agreement with a study done in Ghana which found out that the willingness and ability of young women to use FP methods and services were affected often negatively, by factors operating within and across each level and some of those factors included peer in uence, non-spousal support and support and lack of support from relative (11). It also indicates a need to increase on socializing ability of the women using the method with those not yet using the method to proof their good experiences so as to increase on the IUD usage.…”
Section: Experiences Faced By Wra Using Iud Contraceptivesupporting
confidence: 91%
“…However, for mothers who experienced challenges and side effects discouraged other mothers from using IUD. This is in agreement with a study done in Ghana which found out that the willingness and ability of young women to use FP methods and services were affected often negatively, by factors operating within and across each level and some of those factors included peer in uence, non-spousal support and support and lack of support from relative (11). It also indicates a need to increase on socializing ability of the women using the method with those not yet using the method to proof their good experiences so as to increase on the IUD usage.…”
Section: Experiences Faced By Wra Using Iud Contraceptivesupporting
confidence: 91%
“…Nor have studies formally investigated a more comprehensive set of dimensions comprising stigma, beyond enacted and internalized stigma, that may relate to young peoples’ SRH perceptions and experiences, especially in sociocultural contexts like Ghana. In our own prior qualitative analysis of data from this same cohort of young Ghanaian women, 33 participants alluded to lived experiences which we believe support a need for a more nuanced understanding of stigma as a potentially unique phenomenon. Taking a broad and initial perspective using a grounded theory approach, we previously found that influences operating at the community and macro levels of young women’s environments, including unaccepting social, cultural and religious norms around premarital sexual activity, pregnancy, and abortion, shaped FP decision- making and behaviors.…”
Section: Introductionmentioning
confidence: 86%
“…Frequently depicted as a series of concentric circles, the SEM includes: (1) individual characteristics, knowledge, attitudes, and skills (Individual level) at the centre; (2) relationships with family, friends, and those within their close social networks (Interpersonal level); (3) the structural, cultural, and services environment within their “local” community (Community level); and (4) the greater social, cultural, economic, and policy structures (Societal level) within which an individual exists (McLeroy et al, 1988; Smedley and Syme, 2000). Though widely applied in health behavior research (Challa et al, 2018; Clark et al, 2017; Larios et al, 2009), we only found one study that explicitly applied the SEM to frame factors influencing maternal care-seeking behaviors (Shahabuddin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%